B-type natriuretic peptide and outcome of weaning from mechanical ventilation - Mahmoud Nashed Mahmoud Abdelsalam; Amal Rizk; Khaled Abdelwahab; Mervat Khalaf (Cairo : Mahmoud Nashed Mahmoud Abdelsalam, 2017)
rediction of weaning success remains a major clinical challenge. Cardiovascular dysfunction could be a major underlying mechanism of weaning failure. Recent data suggest that BNP; a marker for cardiovascular dysfunction, may predict the outcome of weaning from assisted mechanical ventilation p(1)(B. BNP variations during spontaneous breathing trial may be of predictive value concerning the outcome of weaning process p(2(B{up00(BAA}p)s
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Critical Care Medicine
Issued also as CD
Keywords: B-type natriuretic peptide; BNP; Outcome of weaning from mechanical ventilation